Chronicle of a Deflation Unforetold - Velde, François R. (Journal of Political Economy, 2009)
Suppose that the nominal money supply could be cut literally overnight. What would happen to prices, wages, and output? Such an experiment was carried out three times in France in 1724, resulting in a cumulative 45 percent cut. Prices adjusted instantaneously and fully on the foreign exchange market. Prices of commodities and of manufactured goods and industrial wages fell slowly, over many months, and not by the full amount of the nominal reduction. The industrial sector experienced a contraction of 30 percent. When the government changed course and increased the nominal money supply overnight by 20 percent, prices responded more, and industry rebounded.